Urine analysis in monoclonal gammopathies at diagnosis: settling cut-off values - Vidal-Pla Mònica; Nuez-Zaragoza Elisa; Bhambi Indira; Aguadero Vicente (Advances in Laboratory Medicine)
Laboratory testing has an extensive role in the diagnosis of monoclonal gammopathies. Since the last updates of the International Myeloma Working Group (IMWG) guidelines for the diagnosis of monoclonal gammopathies, debate has arisen as to whether urine analysis remains relevant for the diagnosis of these entities.